Islamic Values as Foundation Management Based School at Madrasah - Jufri (SYATTAR, 2024)
This study aims to examine the role of Islamic values as a conceptual foundation for the implementation of School-Based Management (SBM) in madrasas. The research is motivated by the tendency of SBM practices in madrasas to emphasize administrative and technocratic aspects, while the systematic integration of Islamic values remains limited. This study employs a library research method with a theoretical approach by analyzing scholarly literature related to School-Based Management, Islamic Educational Management, and Islamic ethical and value theories. Data were collected from authoritative books, peer-reviewed national and international journal articles, and relevant educational policy documents. Data analysis was conducted through content analysis and theoretical synthesis to identify the relationship between Islamic values and managerial functions in madrasas. The findings indicate that the values of trustworthiness , justice, consultation , responsibility, and ihsan (excellence) are highly relevant to all managerial functions, including planning, organizing, implementation, and evaluation. The integration of these values strengthens managerial effectiveness, fosters an ethical organizational culture, and reinforces the Islamic identity of madrasas. The study concludes that School-Based Management in madrasas will be more contextual, value-oriented, and sustainable when Islamic values are positioned as the core foundation of educational management. This research contributes theoretically to the development of Islamic Educational Management and provides practical insights for madrasah leaders and education policymakers in designing value-based management models responsive to contemporary educational challenges.